AI in Software Engineering: Elevating Developer Experience through Codeium and Copilot - Kanda, Pan (Journal of Research in Science and Engineering, 2025)
Integrating artificial intelligence (AI) into software engineering has revolutionized the software development lifecycle (SDLC). AI-driven tools like Codeium and Copilot have significantly improved developer efficiency by automating repetitive tasks, providing intelligent code suggestions, and enhancing collaboration. However, despite their benefits, these tools have certain limitations, including reliance on large datasets, security concerns, and resistance to adoption. This paper explores the advantages, industry constraints, cost-benefit analysis, and future implications of AI in software engineering, highlighting the transformative role of Codeium and Copilot. We also explore future directions, including scalability, accessibility, and regulatory frameworks, to ensure responsible AI adoption.